Radical prostatectomy after previous transurethral resection of the prostate: robot-assisted laparoscopic versus open radical prostatectomy in a matched-pair analysis - Martinschek, Andreas; Heinzelmann, Kathrin; Ritter, Manuel; Heinrich, Elmar; Trojan, Lutz (Journal of endourology, 2012)
Purpose: To determine whether previous transurethral resection of the prostate (TURP) compromises the surgical outcome and pathologic findings in patient who underwent either radical robot-assisted laparoscopic prostatectomy (RALP) or open retropubic radical prostatectomy (RRP) after TURP, because TURP is reported to complicate radical prostatectomy and there are conflicting data.Patients and Methods: From July 2008 to July 2010, 357 patients underwent RALP. Of these, 19 (5.3%) patients had undergone previous TURP. Operative and perioperative data of patients were compared with those of matched controls selected from a database of 616 post-RRP patients. Matching criteria were age, clinical stage, the level of preoperative prostate-specific-antigen, the biopsy Gleason score, the American Society of Anesthesiologists classification score, and prostate volume assessed during transrectal ultrasonography. All RRP and RALP procedures were performed by experienced surgeons.Results: Mean time to prostatectomy was 67.4 months in the RALP group and 53.1 months in the RRP group. Mean operative time was 217±51.9 minutes for RALP and 174±57.7 minutes for RRP (P<0.05). The overall positive surgical margin rate was 15.8% in both groups (pT2 tumors: 10.5% for RALP and 5.3% for RRP; P=1.0). Mean estimated blood loss was 333±144 mL in RALP patients and 1103±636 mL in RRP patients (P<0.001). The difference between preoperative and postoperative hemoglobin levels was 3.22±0.98 g/dL for RALP and 5.85±1.95 g/dL for RRP (P=0.0002). The RALP and RRP groups also differed in terms of hospital stay (8.58±1.17 vs 11.74±5.22 days; P=0.0037), duration of catheterization (7.95±5.69 vs 11.78±6.97 days; P=0.0016), postoperative complications according to the Clavien classification system (6 vs 15 patients; P=0.0027), and transfusion rate (0% vs 10.5%; P<0.001).Conclusion: RALP offers advantages over open radical prostatectomy after previous surgery. Although both techniques are associated with adequate surgical outcomes, RALP appeared to be preferable in our population of patients with previous prostate surgery.
Online ahead of print : May 31, 2012
Gesehen am 24.10.2018